Analysis of The Emotional Intelligence Level of PB Target Badminton Athletes in The Sports Development Process - Muhammad Farhan Aulya; Ayu Dewi Setyawati (Journal of Physical Education, Sport, and Human Performance, 2026)
Introduction. This study aims to analyze the emotional intelligence level of PB Target badminton athletes in the sports coaching process, as well as to describe each aspect of emotional intelligence, including intrapersonal, interpersonal, stress management, and adaptability. The study uses a quantitative approach with a descriptive research type. The research subjects were all 15 badminton athletes of PB Target, so the sampling technique used was total sampling. Data collection was conducted through an emotional intelligence questionnaire adapted from the Emotional Quotient Inventory (EQ-i) with a Likert scale. The data were analyzed using the percentage technique to determine the category of the athletes' emotional intelligence level. The results of the study show that the emotional intelligence level of PB Target badminton athletes is in the very strong category. In terms of intrapersonal indicators, all athletes demonstrated excellent abilities in recognizing, understanding, and managing their emotions. The interpersonal indicator is also in the very strong category, as demonstrated by their empathy, communication, and positive social relationships. In addition, the stress management and adaptability indicators show that athletes are able to control pressure, adapt to situations, and make appropriate decisions. Based on these results, it can be concluded that the emotional intelligence of PB Target badminton athletes is very good and plays an important role in supporting the development of performance-oriented sports. Therefore, the development of emotional intelligence needs to be maintained and systematically integrated into athlete development programs.